VAST contest dataset use in education - Whiting, M.A.; North, C.; Endert, A.; Scholtz, J.; Haack, J.; Varley, C.; Thomas, J. (2009 IEEE Symposium on Visual Analytics Science and Technology, 2009)
The IEEE Visual Analytics Science and Technology (VAST) Symposium has held a contest each year since its inception in 2006. These events are designed to provide visual analytics researchers and developers with analytic challenges similar to those encountered by professional information analysts. The VAST contest has had an extended life outside of the symposium, however, as materials are being used in universities and other educational settings, either to help teachers of visual analytics-related classes or for student projects. We describe how we develop VAST contest datasets that results in products that can be used in different settings and review some specific examples of the adoption of the VAST contest materials in the classroom. The examples are drawn from graduate and undergraduate courses at Virginia Tech and from the Visual Analytics ldquoSummer Camprdquo run by the National Visualization and Analytics Center in 2008. We finish with a brief discussion on evaluation metrics for education.